Water treatment using one-dimensional manganese oxide based materials - Zhang, Tong (2013)
In recent years, there has been a growing trend in the usage of nanomaterials to enhance water purification efficiency. One-dimensional (1D) nanostructured manganese oxides and their derivatives have attracted considerable research interest due to their large surface area, adjustable transport properties and chemical specificities. However, separation and recovery of these nanosized materials in heterogeneous systems continue to remain a steep challenge. To overcome the engineering issue, various separation techniques such as free settling, centrifugation, magnetic separation and membrane filtration, have been proposed over the years. This research topic mainly focused on the synthesis and environmental application of 1D nanostructured manganese oxide based materials in the easily separable forms including MnO2 nanowires, magnetic manganese oxide nanocomposites, micro-/nano-structured MnO2 spheres, and manganese oxide nanofibrous membrane. The synthesized materials were characterized and successfully applied in several water treatment processes. Furthermore, the nanomaterials were recycled from the treated water by using different routes, and the related separation mechanisms were also discussed in this dissertation. As a basic material in this research, 1D cryptomelane-type manganese oxide (K-OMS-2) nanowires were synthesized via a hydrothermal method. The nanowires can be used as an adsorbent or oxidant for water treatment. After coupling with Fe3O4 nanoparticles, the synthesized K-OMS-2/Fe3O4 nanocomposites became a multifunctional material with adsorption, oxidation and magnetic properties. Batch tests were conducted to evaluate the performance of the synthesized materials under different conditions. Due to the increased specific surface area, the synthesized K-OMS-2/Fe3O4 nanocomposites exhibited higher oxidation and adsorption capacities for the removal of arsenic as compared to the K-OMS-2 nanowires. To further enhance the oxidation capacity of the material, 1D MnO2 nanowires were synthesized using a similar hydrothermal method based on the synthesis of K-OMS-2 nanowires. Moreover, a novel hybrid process combining the 1D MnO2 nanowires oxidation and microfiltration was adopted to remove bisphenol A (BPA). The effects of pH, humic acid (HA) and coexisting metal ions on the removal rate of BPA were investigated, and membrane fouling mechanism caused by the MnO2 nanowires was also discussed. To further enhance the specific surface area of manganese oxides, a catalytic oxidation route was conducted to synthesize 3D MnO2 spheres, which was assembled by 1D manganese oxide nanowires on the surface. Experimental results indicated that the adsorption and oxidation abilities of the MnO2 sphere were increased as compared to the 1D K-OMS-2 nanowires, and a dead-end microfiltration setup was also used to investigate the separability of the material.